2019
DOI: 10.1103/physrevb.99.014421
|View full text |Cite
|
Sign up to set email alerts
|

Singlet ground state in the alternating spin- 12 chain compound NaVOAsO4

Abstract: We present the synthesis and a detailed investigation of structural and magnetic properties of polycrystalline NaVOAsO4 by means of x-ray diffraction, magnetization, electron spin resonance (ESR), and 75 As nuclear magnetic resonance (NMR) measurements as well as density-functional band structure calculations. Temperature-dependent magnetic susceptibility, ESR intensity, and NMR line shift could be described well using an alternating spin-1/2 chain model with the exchange coupling J/kB 52 K and an alternation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…A recently discovered class of alternating spin-chain materials includes AgVOAsO 4 [112] and NaVOAsO 4 [113], which have magnetic coupling constants in the 5 meV range. Although here λ is at the upper validity limit of our present simple treatment of the spin chain (Sec.…”
Section: Methodsmentioning
confidence: 99%
“…A recently discovered class of alternating spin-chain materials includes AgVOAsO 4 [112] and NaVOAsO 4 [113], which have magnetic coupling constants in the 5 meV range. Although here λ is at the upper validity limit of our present simple treatment of the spin chain (Sec.…”
Section: Methodsmentioning
confidence: 99%
“…Correlation effects in the V 3d shell were taken into account on the mean-field DFT+U level with the on-site Coulomb repulsion U d = 4 eV, Hund's exchange J d = 1 eV, and around-mean-field doublecounting correction. [22] III. RESULTS AND ANALYSIS A. X-ray Diffraction Figure 2 displays the powder XRD pattern of NaVOPO 4 at three different temperatures (T = 600 K, 300 K, and 17 K).…”
Section: Methodsmentioning
confidence: 99%
“…We compare NaVOPO 4 with the isostructural compounds NaVOAsO 4 arXiv:1909.00117v1 [cond-mat.str-el] 31 Aug 2019 and AgVOAsO 4 to understand the underlying structureproperty relationship. [22][23][24][25] The aforementioned V 4+ phosphates and arsenates crystallize in the monoclinic crystal structure (space group P 2 1 /c). One peculiarity of this series is that the structural chains formed by the corner-sharing VO 6 octahedra do not represent the magnetic chains [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the magnetism perspective, the crucial feature of AVOXO 4 is that their structural chains are not the direction of predominant magnetic interactions, even though the intrachain V-V distances are much shorter than the interchain ones [11,12]. It has been shown that monoclinic NaVOXO 4 [13,14] and AgVOAsO 4 [11,15], as well as triclinic ε-LiVOPO 4 [16], all adopt an intriguing pattern of crossed bond-alternating spin chains, which are perpendicular to the structural chains. These compounds reveal a field-induced quantum phase transition and an unusual double-dome regime of Bose-Einstein condensation (BEC) of magnons in high magnetic fields [12].…”
Section: Introductionmentioning
confidence: 99%